Descriptive analysis of depression among adolescents in Huangshi, China - Xiaozhi Zhang; Yueming Yan; Zhuofan Ye; Jumin Xie (BMC Psychiatry, 2023)
Abstract Background More adolescents suffered from depressive disorder, and what was worse, the morbidity increased annually. The situation was getting worse during COVID-19 pandemic. The prevalence of depression among adolescents in China has increased a lot due to social and economic development, family-associated reasons, academic stress, interpersonal relationships, and so on. Objective This study aimed to determine the prevalence, gender differences, risk factors, and abnormal illness behaviors of depression among adolescents in Huangshi, China. Methods A descriptive analysis was conducted based on the data from clinical interviews and self-reports by the patients. Depression was assessed and diagnosed using the DSM-5 Diagnostic and Statistical Manual of Mental Disorders. Results Depression was most frequently seen in 674 patients with mental illnesses (282, 41.84%). The male-to-female ratio was 1:2.44, and their age ranged from 9 to 18. The majority of patients are in high school (261/282, 92.55%), and the highest morbidity occurred at 16 years. More cases were diagnosed in urban than in rural areas. Genetic factors, school violence, academic stress, sleep disorders, and family-related factors were essential factors leading to depression among adolescents. Most patients had sleep disorders (84.75%). In family-related factors, left-behind children and unrecognized/misunderstood by their families were prominently diagnosed with depression. A large portion of individuals with depression felt apathetic, solitary, and sluggish and were unable to study, work, and live normally (212/282, 75.18%); they even committed suicide or attempted suicide (228/282, 80.85%) and inflicted self-harm (146/282, 51.77%). Conclusions An increasing trend of depression has been observed since 2018, especially in 2021. This depression has led to suicide or suicidal attempts and self-harm, reflecting the severity of mental health among adolescents in Huangshi. Therefore, this study aimed to draw the attention of society, families, and schools to the importance of mental health among adolescents, providing guidance and references for the prevention, diagnosis, and treatment of young depressive disorders in China.